Hukum Pertahanan Dan Keamanan Negara “State Defense And Security Law” - Eriz Syawaldi; Irwan Triadi (Universitas Katolik Widya Karya Malang, 2023)
This research is motivated by the State Defense and Security Law contained in Article 30 paragraphs (1) and (2) of the 1945 Constitution which requires citizens to participate in efforts to protect and secure the state. State security is implemented through the entire system, protecting the people with a system national. The army and police are the main forces, the people are the supporting forces, so that state protection and security are structured based on the concept of state protection. The type of legal research carried out in a normative juridical manner is normative juridical where law is conceptualized as what is written in statutory regulations (law in books) or law is conceptualized as rules or norms which are benchmarks for behavior that is considered appropriate. The legal materials used are the 1945 Constitution, textbooks, foreign journals, opinions of scholars, legal cases, and symposiums held by relevant experts. The legal material analysis technique used in this research is interpretation, namely the use of juridical methods in discussing a legal problem. From this study it can be drawn back to the discussion that the State Defense and Security Law as regulated in Article 30 paragraphs (1) and (2) of the 1945 Constitution is a defensive measure which requires citizens to participate in state defense and security. These efforts are structured based on the concept of defending the country in order to foster a spirit of nationalism and patriotism in every Indonesian citizen